Le degré de compréhension d’élèves de 3e secondaire sur trois formes de documents de type argumentatif - Carignan, Isabelle; Grenon, Vincent (Canadian Journal of Education/Revue canadienne de l’éducation, 2012)
When reading a newspaper, a Word document, or a website, a reader uses different mechanisms to keep track of his or her comprehension. However, is there a real difference between reading comprehension of text on a screen and text on paper? Does the support or the textual structure have an influence on reading comprehension? To answer these questions, an exploratory research was conducted. We used the recall technique as a methodological tool. The data was first analyzed qualitatively with macro-propositional analysis. Quantitative analysis using nonparametric statistical methods was also used. The results showed that nearly half of the participants (n = 12) had a better understanding of hypertext and a quarter of the participants gained a better understanding of the text on paper. However, in terms of the overall average obtained, this study found that the participants had a better reading comprehension of the paper text. Keywords: Reading comprehension, reading on a screen, reading on paper, secondary education, argumentative text